The Effect of Government Regulations and Tax Policies on the Business Life of Shops in Suryakencana Market, Bogor - Ujang Badru Jaman; Arief Fahmi Lubis; Yana Priyana (West Science Law and Human Rights, 2023)
This research delves into the intricate relationship between government regulation, tax policy, and the business life of shops in Suryakencana Market, Bogor. Employing a mixed-methods approach that combines quantitative survey data, financial analysis, and qualitative insights from interviews, this study uncovers the multifaceted impact of government regulations and tax policies on businesses in the market. The results reveal that government regulations impose a significant regulatory burden and compliance costs on businesses, particularly affecting small enterprises. Industry-specific effects further highlight the need for tailored approaches to regulation. Additionally, tax policies influence business operations, with businesses often passing tax costs to consumers, and incentives promoting profitability. Cross-border taxation issues pose challenges to businesses engaged in international trade. These findings provide valuable insights for policymakers and stakeholders, emphasizing the importance of streamlining compliance procedures, supporting small businesses, and offering incentives for innovation and job creation to foster a conducive environment for business growth and sustainability in Suryakencana Market.